PENGENDALIAN INTERNAL SISTEM AKUNTANSI PENGGAJIAN MI NURUL BAHRI ALMASHOOLIH - Restiani Restiani; Diah Vitaloka Adam (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The purpose of this research is to find out whether the implementation of the internal control of the payroll accounting system at MI Nurul Bahri Almashoolih is in accordance with the theory. This research is a qualitative research using descriptive techniques and case studies at MI Nurul Bahri Almashoolih. Data collection is done through observation, interviews, and documentation. The first step is to describe the payroll system that exists at MI Nurul Bahri Almashoolih. The second stage is to compare theory with practice in the payroll accounting system of MI Nurul Bahri Almashoolih. Based on the findings of the data analysis, it is clear that the internal control of the MI Nurul Bahri Almashoolih payroll system is not in accordance with the theory. Because one of them is a dual function task.